The role of adjuvant therapy in Stage I ovarian cancer - Hreshchyshyn, M M; Park, R C; Blessing, J A; Norris, H J; Levy, D; Lagasse, L D; Creasman, W T (American journal of obstetrics and gynecology, 1980)
Women with Stage I epithelial carcinoma of the ovary were initially treated by an extirpative operation and were subsequently randomized to either no further treatment, radiotherapy, or chemotherapy. Only two patients (6%) treated with chemotherapy developed recurrence, compared to five (17%) and seven (30%) patients in the no-treatment and radiotherapy regimens, respectively (P < 0.05). All patients, with the possible exception of those with Stage IA(1)g1, appeared to benefit from adjuvant chemotherapy compared to no treatment or radiotherapy.